Assessing straw digestate as feedstock for bioethanol production. (June 2020) - Stoumpou, Vasileia; Novakovic, Jelica; Kontogianni, Nikoleta; Barampouti, Elli Maria; Mai, Sofia; Moustakas, Kostantinos; Malamis, Dimitris; Loizidou, Maria
Abstract: Anaerobically digested agricultural waste, such as straw digestate, still consists of residual lignin and carbohydrates that may be utilised as substrate for sugars production and alcoholic fermentation. Chemical pretreatment combined with enzymatic hydrolysis was investigated as an alternative valorisation route for digestate. Acid pretreatment along with enzymatic hydrolysis was found to yield low sugars recoveries (2–39%), casting doubt on its suitability for ethanol production. In contrary, alkaline pretreatment and enzymatic hydrolysis is a better approach with elevated saccharification yields reaching up to 72%. Ethanol fermentation of alkaline pretreated digestate presented yields up to 65% consuming all the available glucose, implying that no inhibitory factors are present. Conclusively, according to the experimental results the perspective of a new integrated system is enforced. This system combines ethanol production with anaerobic digestion simultaneously producing energy in the form of ethanol and methane and improving the overall energy balance. Highlights: Anaerobic digestate proved to be a promising feedstock for bioethanol production. Alkaline pretreatment improved saccharification yield of straw digestate. Acid pretreatment of digestate was inefficient in terms of sugars recovery. Autoclave time and enzyme loading control ethanol production from digestate.